Assistance in Preparing the Curriculum and Learning Tahfidz Al-Qur'an at the Ilyasiyah As'adiyah Islamic Boarding School in Santan Tengah Kutai Kartenegara - Bunyamin Bunyamin; Riswan Riswan; Sri Ayu Rayhaniah (Penerbit Widina, Widina Media Utama, 2024)
Islamic boarding schools are traditional educational institutions with the oldest Islamic characteristics in the archipelago. Its presence is expected to be able to improve and improve Islamic traditions. Pondok Tahfidz Ilyasiyah As'adiyah, Santan Tengah Village has the potential to become a superior Islamic tahfidz boarding school. To improve the achievements of students to a higher level such as MTQ at the district/city, provincial, and even national levels, even harder efforts are needed from the administrators and coaches to organize more systematic and well-programmed tahfidz education and teaching through a curriculum that is in accordance with the conditions of the students.ABSTRAKPondok pesantren adalah lembaga Pendidikan tradisional dengan ciri khas Islam tertua di Nusantara. Kehadirannya diharapkan mampu memperbaiki dan meningkatkan tradisi keislaman. Pondok Tahfidz Ilyasiyah As’adiyah Desa Santan Tengah memiliki potensi untuk menjadi pondok pesantren tahfidz unggulan. Untuk meningkatkan prestasi para santri ke level yang lebih tinggi lagi seperti MTQ tingkat kabupaten/kota, provinsi, bahkan nasional maka diperlukan upaya yang lebih keras lagi dari para pengurus dan pembina untuk menyelenggarakan pendidikan dan pengajaran tahfidz yang lebih sistematis dan terprogram dengan baik melalui kurikulum yang sesuai dengan kondisi para santri.